LEVELS OF DIABETES BLOOD SUGAR WITH TYPE OF CATARACT - Indah Lestari; Fifiyahpuahsari Fifiyahpuahsari (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2019)
Diabetes mellitus was a disease with macro and micro risk of angiopathy, which includes the impact of causing cataracts. Diabetic patients with high sugar levels have a greater chance of developing cataracts at a younger age and certain tendencies towards cataract type. The aim of the study was to analyze the correlation between diabetes blood sugar levels and cataract type. The research design was correlation analysis with Cross-Sectional approach. Samples in the study were some cataract patients who had a history of diabetes mellitus in Surabaya Undaan Eye Hospital as many as 125 people, it was taken using consecutive sampling technique, and fulfilling the criteria of the study (age range 45 - 65 years, have complete medical records related to the continuity of sugar examination results in blood, the incidence of cataracts is not caused by congenital cataracts, juveniles, due to trauma, chemical exposure to UV radiation). Independent variable was the blood sugar level of Diabetes mellitus and the Dependent variable was cataract type. The instruments used were laboratory tests related to blood sugar levels, and medical diagnosis related to cataract type. Data were analyzed by Spearman rho, with a significant value <0.05. The results showed a close association between diabetes and cataracts, where as many as 47.2% with high blood sugar levels, 40% with nuclear cataract type and from 59 respondents with high blood sugar levels 26 people experienced nuclear cataract type, with rho value = 0.001. The mechanism of glucose toxicity in Diabetes Mellitus which causes cataracts can go through three paths: increased activity of the aldose reductase enzyme which causes the formation of sugar alcohol, sorbitol and galactitol in crystalline lenses; through the non-enzymatic replication process; and at high blood glucose levels a glucose oxidation process will occur which causes oxidative stress conditions. Maintenance of managing blood sugar levels must be a concern for diabetics. Keywords: Blood Sugar Level, Diabetes Mellitus, Type of Cataract